FREE VIBRATION ANALYSIS OF PLANE STRESS/STRAIN MODELS USING KRIGING-BASED FINITE ELEMENT METHOD - Tjong, Wong Foek; Christiana, Christiana (Program Studi Magister Teknik Sipil - Petra Christian University, 2025)
Kriging-based finite element method (K-FEM) is an enhancement of standard FEM that employs Kriging interpolation over nodal points both within and outside the element domain. This method significantly increase the accuracy of conventional FEM. This paper presents the development and applications of the K-FEM to free vibration analysis of plane bodies with negligible damping. Six benchmark problems are examined: a cantilever beam, a simply supported beam, an arch, a shear wall, a slope, and a tapered cantilever plate with a hole. The computed natural frequencies and mode shapes demonstrate close agreement with reference solutions. Convergence toward the reference values is achieved as the mesh is refined and the degree of the polynomial basis increases, while additional DOI layers exert only a minor influence. These findings confirm that K‑FEM is a viable alternative to the conventional FEM for free vibration analysis of plane stress and plane strain models.